Modeling boron dose loss in sidewall spacer stacks of complementary metal oxide semiconductor transistors. (December 2016) - Essa, Z.; Pelletier, B.; Morin, P.; Boulenc, P.; Pakfar, A.; Tavernier, C.; Wacquant, F.; Zechner, C.; Juhel, M.; Autran, J.L.; Cristiano, F.
Highlights: In presence of silicon oxide/nitride capping bilayer we observe substantial boron loss in silicon junction submitted to thermal anneal. Boron dose loss is driven by the segregation at the interface, and the enhanced boron diffusivity in oxide which is modulated by the hydrogen content. We have developed a model to describe the hydrogen dynamics in the samples and the boron diffusivity as function of the hydrogen content. We have postulated that boron diffuses in oxide through long hop mechanism, considering mobile and immobile boron species. Abstract: The presence of capping materials during annealing (activation for example) can substantially impact the silicon junction profiles of Complementary Metal Oxide Semiconductor Field Effect Transistors (CMOSFET), depending on the nature of these layers. In this paper we specifically investigated the boron out-diffusion from a silicon junction into the silicon oxide in presence of a silicon oxide/silicon nitride capping bi-layer similar to the stacks used to form sidewall spacers. After 120 s anneal we observed with secondary ion mass spectrometry (SIMS) substantial boron dose loss in silicon and segregation at the silicon oxide interface related to oxide and nitride material properties, in particular to the hydrogen concentration. We then modeled the boron profiles in both silicon and oxide as a function of the hydrogen static and dynamic in the materials. The exponential-like boron diffusion profiles observed in oxide are reproduced by introducing a long hop mechanism mediated with hydrogen-related defects (HRDs).